2014
DOI: 10.1039/c3ra43280g
|View full text |Cite
|
Sign up to set email alerts
|

First example of diglycolamide-grafted resins: synthesis, characterization, and actinide uptake studies

Abstract: Two diglycolamide (DGA)-functionalized chelating extraction resins were prepared for the first time by grafting onto a silica matrix and were evaluated for their actinide ion uptake behavior. The resins with one and two DGA moieties, termed as resin-I and resin-II, were quite efficient for the actinide ions, particularly the tri-and the tetravalent ions in a way similar to the diglycolamide extractants. The hexavalent UO 2 2+ ion was poorly sorbed onto the resins. The resins were characterized by thermal analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…26 In the case of DGA-grafted silica, the elution of Am(III) was also straightforward. 25 To clarify this, the poly(methacryloyl-DGA) samples were treated with HNO 3 and subjected to SAXS analysis. From the SAXS profiles in Figure 3, it is clear that distinct changes in the physical structure of the poly(methacryloyl-DGA) matrix occur upon HNO 3 treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 In the case of DGA-grafted silica, the elution of Am(III) was also straightforward. 25 To clarify this, the poly(methacryloyl-DGA) samples were treated with HNO 3 and subjected to SAXS analysis. From the SAXS profiles in Figure 3, it is clear that distinct changes in the physical structure of the poly(methacryloyl-DGA) matrix occur upon HNO 3 treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is also important to note that Am 3+ could not be deloaded from the poly(methacryloyl-DGA) matrix using the disodium salt of EDTA, while deloading from organic-phase-containing methacryloyl-DGA was rather easy . In the case of DGA-grafted silica, the elution of Am(III) was also straightforward …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding actinides, use of trialkyl phosphine oxide functionalized task specific ionic liquids for the recovery of actinides [5] and separation of minor actinides from acidic PUREX waste solution using bis (2-ethylhexyl) sulfoxides have also been reported [6]. Mohapatra et al [7] investigated the uptake of actinides using diglycolamidegrafted resins as stationary phase. Several studies also reported recovery of lanthanides and actinides using octyl(phenyl)-N,N-diisobutylcarbamoylmethylphosphine oxide (CMPO) as the stationary phase [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%